INNOVATIVE SIGNIFICANCE OF MOBILE APPLICATIONS FOR ENSURING HIGH SPORTS RESULTS IN COACHING PRACTICE (on the example of basketball) (Scientific journal of the Fergana State University, 2026)
This article examines the impact and innovative significance of using mobile applications in coaching practice to achieve high sports results (on the example of basketball).